Academic Resilience and Academic Engagement as Predictors of Academic Burnout among Postgraduate Students at the University of Cape Coast, Ghana - Amponsah, Mark Owusu; Ampofo, Kyei Anane; Annan-Brew, Ruth Keziah; Dadzie, Justice (International Journal of African Higher Education, 2024)
This article investigates the predictive roles of academic resilience and academic engagement in academic burnout among postgraduate students at the University of Cape Coast, Ghana. Guided by seven objectives transformed into three research questions and four hypotheses, a descriptive survey design with a quantitative approach was employed. The population consisted of 847 postgraduate students, with 265 participants selected through stratified and simple random sampling. Questionnaires were adapted to measure the study objectives, and data were analysed using simple linear regression and multiple linear regression analyses. The findings revealed significant predictive relationships between academic resilience, academic engagement, and academic burnout. A positive relationship was also established between academic resilience and academic engagement. The study concluded that academic resilience and engagement play crucial roles in predicting and understanding academic burnout among postgraduate students. It recommended collaborative efforts between university management, lecturers, and counsellors to implement policies and measures to address this issue.